Silver Nanoparticles Biosynthesized With Salvia officinalis Leaf Exert Protective Effect on Hepatic Tissue Injury Induced by Plasmodium chabaudi - Metwally, Dina M.; Alajmi, Reem A.; El-Khadragy, Manal F.; Al-Quraishy, Saleh (Frontiers in Veterinary Science, 2021)
Malaria is an important health problem in subtropical and tropical areas around the world. Infection with protozoan parasites of the Plasmodium genus, which grow inside host erythrocytes, causes malaria and may lead to morbidity and mortality. Liver tissue plays an important role in the pathogenesis of malaria and is closely involved in parasitic pre-erythrocytic development. Numerous published studies have demonstrated that the liver is not only the source of Plasmodium parasites prior to erythrocytic growth but is also a primary immune effector toward the blood stage of the malaria life cycle. Despite efforts to improve antimalarial drugs and vaccines, Plasmodium species that cause severe malaria are being detected increasingly frequently in endemic regions. In this study, Salvia officinalis (S. officinalis) leaf extract was employed to synthesize silver nanoparticles (Ag-NPs). This method is eco-friendly and represents a single-step technique for the biosynthetic process; therefore, it has attracted considerable attention. Accordingly, we biosynthesized Ag-NPs with extract of the S. officinalis leaf and examined the antimalarial activity of these nanoparticles in a murine model of Plasmodium chabaudi malaria (P. chabaudi malaria). Forty mice were chosen and classified into four types: infected group, healthy control, pretreated mice infected after treatment with 50 mg/kg of S. officinalis leaf extract-biosynthesized Ag-NPs for two weeks, and post-treated mice infected before treatment with 50 mg/kg of S. officinalis leaf extract-biosynthesized Ag-NPs (administered daily for 7 d). In this study, both pre-treatment and post-treatment with Ag-NPs produced a substantial reduction in parasitemia relative to the infected group. We investigated the antiplasmodial and hepatoprotective effects of S. officinalis leaf extract-biosynthesized Ag-NPs on P. chabaudi-induced inflammation and hepatic oxidative stress markers.